EIF2A-dependent translational arrest protects leukemia cells from the energetic stress induced by NAMPT inhibition. Issue 1 (December 2015) - Zucal, Chiara; D'Agostino, Vito; Casini, Antonio; Mantelli, Barbara; Thongon, Natthakan; Soncini, Debora; Caffa, Irene; Cea, Michele; Ballestrero, Alberto; Quattrone, Alessandro; Indraccolo, Stefano; Nencioni, Alessio; et al.
Abstract Background Nicotinamide phosphoribosyltransferase (NAMPT), the rate-limiting enzyme in NAD+ biosynthesis from nicotinamide, is one of the major factors regulating cancer cells metabolism and is considered a promising target for treating cancer. The prototypical NAMPT inhibitor FK866 effectively lowers NAD+ levels in cancer cells, reducing the activity of NAD+ -dependent enzymes, lowering intracellular ATP, and promoting cell death. Results We show that FK866 induces a translational arrest in leukemia cells through inhibition of MTOR/4EBP1 signaling and of the initiation factors EIF4E and EIF2A. Specifically, treatment with FK866 is shown to induce 5′AMP-activated protein kinase (AMPK) activation, which, together with EIF2A phosphorylation, is responsible for the inhibition of protein synthesis. Notably, such an effect was also observed in patients' derived primary leukemia cells including T-cell Acute Lymphoblastic Leukemia. Jurkat cells in which AMPK or LKB1 expression was silenced or in which a non-phosphorylatable EIF2A mutant was ectopically expressed showed enhanced sensitivity to the NAMPT inhibitor, confirming a key role for the LKB1-AMPK-EIF2A axis in cell fate determination in response to energetic stressvia NAD+ depletion. Conclusions We identified EIF2A phosphorylation as a novel early molecular event occurring in response to NAMPT inhibition and mediating protein synthesis arrest. In addition, our data suggest that tumors exhibiting an impaired LBK1- AMPK- EIF2A response may be especially susceptible to NAMPT inhibitors and thus become an elective indication for this type of agents.